Evolution and Transformation of Uterine Transplantation: A Systematic Review of Surgical Techniques and Outcomes - Escandón, Joseph M.; Bustos, Valeria P.; Santamaría, Eric; Langstein, Howard N.; Ciudad, Pedro; Hernandez-Alejandro, Roberto; Moore, Richard G.; Leckenby, Jonathan I.; Manrique, Oscar J. (Journal of Reconstructive Microsurgery, 2021)
Background Uterine transplantation (UTx) is acknowledged to be on the second (2A) of five steps of development in accordance with the staging system for the evaluation of surgical innovations. Accordingly, we aimed to systematically review the available evidence of the surgical techniques and outcomes of UTx in terms of graft survival.Methods A comprehensive search was conducted across PubMed Medline, Cochrane-EBMR, Scopus, Web of Science, and CENTRAL through November 2020.Results Forty studies, reporting 64 recipients and 64 donors, satisfied inclusion criteria. The surgical time and the estimated blood loss were 515 minutes and 679 mL for graft procurement via laparotomy, 210 minutes and 100 mL for laparoscopic-assisted graft harvest, and 660 minutes and 173 mL for robotic-assisted procedures, respectively. Urinary tract infections (n = 8) and injury to the urinary system (n = 6) were the most common donor complications. Using the donor's internal iliac system, two arterial anastomoses were performed in all cases. Venous outflow was accomplished through the uterine veins (UVs) in 13 cases, a combination of the UVs and the ovarian/uteroovarian veins (OVs/UOVs) in 36 cases, and solely through the OVs/UOVs in 13 cases. Ischemia time was 161 and 258 minutes when using living donors (LD) and deceased donors (DD), respectively. Forty-eight uteri were successfully transplanted or fulfilled the purpose of transplantation, 41 from LDs and 7 from DDs. Twenty-five and four live childbirths from LDs and DDs have been reported, respectively.Conclusion UTx is still experimental. Further series are required to recommend specific surgical techniques that best yield a successful transplant and reduce complications for donors and recipients.
Keywords: uterus; organ transplantation; infertility; female; anastomosis